Stigma and Sexual Health Risk in HIV-Positive African American Young Men Who Have Sex with Men - Radcliffe, Jerilynn (AIDS Patient Care STDS, 2010)
Understanding the multiple forms of stigma experienced by young HIV-positive African American men who have sex with men and how they relate to sexual risk behaviors is essential to design effective HIV prevention programs. This study of 40 African American young MSM found that 90% of those surveyed experienced sexual minority stigma, 88% experienced HIV stigma, and 78% experienced dual stigma. Sexual minority stigma was characterized by experiences of social avoidance, and HIV stigma, by shame. Individuals with high HIV stigma were significantly more likely to engage in unprotected sex while high or intoxicated. Associations between stigma and sexual practices were examined; youth endorsing higher levels of sexual minority stigma engaged in less insertive anal intercourse. Individuals endorsing more HIV stigma reported more receptive anal intercourse. These findings support the development of stigma-informed secondary prevention interventions for African American HIV-positive young MSM.